Description of the modern state of informatization of Ukraine - Жарова, О. В.; Карпенко, С. В.; Ткаліч, О. П.; Ткаліч, О. В. (Problems of Informatization and Control, 2008)
The question of the modern state of informatization is considered in Ukraine, the analysis of normative base is conducted for development of informatization in Ukraine and Conception of the national program of informatization. Measures are offered for forming of national infra-structure of informatization and development of policy and organizational-pravovogo zabezpe-chennya informatization, and also basic measures on informatization of science, education, culture and international cooperation